2019
DOI: 10.1080/0886022x.2019.1595645
|View full text |Cite
|
Sign up to set email alerts
|

High neutrophil/lymphocyte ratio is associated with poor renal outcomes in Japanese patients with chronic kidney disease

Abstract: Background: Several studies have shown that the neutrophil/lymphocyte ratio (NLR) is a marker that reflects the state of systemic inflammation. A high NLR was reported to be associated with cardiovascular events and mortality. However, little is known about the association between NLR and kidney disease progression in patients with chronic kidney disease (CKD). Therefore, the aim of the present study was to determine whether NLR is associated with renal outcomes in CKD patients. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 27 publications
8
58
0
Order By: Relevance
“…The association of biomarkers of in ammation with kidney function decline has been documented in several studies [2,3] and also reported in the eGFR Study, a longitudinal study of adult Indigenous Australians [4]. Some recent studies have shown a possible association of elevated concentrations of white blood cells with kidney function decline [5,6] and others have shown that the neutrophil/lymphocyte ratio, a marker of systemic in ammation, may be associated with poor renal outcomes [7,8]. Furthermore, there is also emerging evidence of an association of abnormal liver function tests with decline in eGFR and increasing albuminuria [9] The eGFR study was a longitudinal study of 654 Indigenous Australian adults from more than 20 sites in urban, regional, and remote Australian regions known to have high incidence of dialysis requiring ESKD, and participants were selected across ve strata of health, diabetes status, and kidney function [10][11][12].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The association of biomarkers of in ammation with kidney function decline has been documented in several studies [2,3] and also reported in the eGFR Study, a longitudinal study of adult Indigenous Australians [4]. Some recent studies have shown a possible association of elevated concentrations of white blood cells with kidney function decline [5,6] and others have shown that the neutrophil/lymphocyte ratio, a marker of systemic in ammation, may be associated with poor renal outcomes [7,8]. Furthermore, there is also emerging evidence of an association of abnormal liver function tests with decline in eGFR and increasing albuminuria [9] The eGFR study was a longitudinal study of 654 Indigenous Australian adults from more than 20 sites in urban, regional, and remote Australian regions known to have high incidence of dialysis requiring ESKD, and participants were selected across ve strata of health, diabetes status, and kidney function [10][11][12].…”
Section: Introductionmentioning
confidence: 83%
“…Some studies have showed that elevated WBC count was a strong predictor of kidney function decline [5], high monocyte count was signi cantly associated with risks of incident CKD and CKD progression to ESKD [6] and low WBC count was independently associated with CKD progression in the elderly [38]. Other studies have demonstrated the potential role of the high neutrophil/lymphocyte ratio as a predictor of poor renal outcomes [7,8]. However, in a study of in ammatory markers including hsCRP, WBC count and ferritin, hsCRP and ferritin strati ed by albumin associated with RRT and rapid renal progression, but WBC count was not associated with renal outcomes [39].…”
Section: Discussionmentioning
confidence: 99%
“…Yoshitomi et al, in their study, demonstrated that NLR was correlated with higher CRP levels, lower eGFR, and the presence of ischemic heart disease (IHD). These findings suggested that high NLR reflects chronic inflammation and poorer renal outcomes [3]. The presence of IHD also might be associated with poorer prognosis in CKD patients because CVD was known to be the most common causes of death in patients' with declined kidney function [7].…”
Section: Discussionmentioning
confidence: 98%
“…The fact that NLR is simply calculated from easily available complete blood count makes it an interesting biomarker in assessing and detecting inflammatory conditions in dialysis patients [2]. Of note, very few studies have addressed the relationship between NLR and kidney disease progression in patients with CKD [3].…”
Section: Introductionmentioning
confidence: 99%
“…In CKD patients, neutrophil-tolymphocyte ratio, an inexpensive and convenient available inflammatory marker has also emerged as a prognostic factor for adverse renal events. In the Asian population, NLR is associated with the risk of progression towards end-stage renal disease [18,19].…”
Section: Introductionmentioning
confidence: 99%